Fact checking, democrazia e giustizia sociale - De Sario, Nadia (Filosofia Morale/Moral Philosophy, 2025)
Is free expression damaging our democracy? Or is free expression the essence of our societies? The fact checking mechanisms and all its complications present us with a challenge on the very concept of democracy, which has changed during centuries. For these reasons, the paper tries to explore the limits between free speech and hate speech, all questioning the justice of fact checking also referring to the different ideas of democracy.